Gotong Royong dalam Membangun Tanggung Jawab Menjaga Lingkungan dan Kebersihan Desa di Era Modern - Yeni Vitrianingsih; Zilfa Fadila Qotrun Nada; Nelud Darajaatul Aliyah; Ella Anastasya Sinambela; Mufaizah Mufaizah (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
Mutual cooperation (gotong royong) is a social value that reflects togetherness, concern, and solidarity in community life, particularly in maintaining a clean village environment. This community service activity aims to build environmental awareness and increase the active participation of villagers in maintaining cleanliness by strengthening the culture of mutual cooperation. The results of the activity indicate that the implementation of mutual cooperation can increase community involvement, strengthen social solidarity, and foster a sense of shared responsibility for environmental cleanliness. This activity also encourages collective awareness and a sense of ownership of the village environment. This service activity proves that strengthening the practice of mutual cooperation based on community participation is effective in supporting efforts to preserve environmental cleanliness and strengthen social ties between residents.